2019
DOI: 10.1093/ee/nvz052
|View full text |Cite
|
Sign up to set email alerts
|

Preference of Peponapis pruinosa (Hymenoptera: Apoidea) for Tilled Soils Regardless of Soil Management System

Abstract: Concerns about global pollinator declines have placed a growing focus on understanding the impact of agriculture practices on valuable native pollinators in these systems. Cultivation practices such as tillage disturb agroecosystems and can have negative impacts on ground-nesting pollinators. The squash bee, Peponapis pruinosa (Say), is a ground-nesting specialist pollinator of Cucurbita (Cucurbitaceae) crops (i.e., pumpkins and squash) that often nests in agricultural fields and thus may be vulnerable to thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…It is certainly the case that dietary specialists (oligoleges) nest near their host plants: squash bee ( Peponapis pruinosa (Say), Apidae) nests occur in squash ( Cucurbita spp.) fields (Julier & Roulston, 2009; Skidmore et al ., 2019); Nomia melanderi nest near alfalfa ( Medicago sativa (Linnaeus)) (Cane, 1997, 2008; Vinchesi et al ., 2013); and Dieunomia triangulifera nest near sunflowers ( Helianthus annuus (Linnaeus)) (Minckley et al ., 1994). Oddly, however, it is not known whether bees actually use the presence or abundance of host‐plant flowers or foliage when choosing where to nest: they may simply be found alongside their host‐plants because of philopatry, or because they share substrate preferences with their host‐plants.…”
Section: Nest‐site Selection: Which Characteristics Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…It is certainly the case that dietary specialists (oligoleges) nest near their host plants: squash bee ( Peponapis pruinosa (Say), Apidae) nests occur in squash ( Cucurbita spp.) fields (Julier & Roulston, 2009; Skidmore et al ., 2019); Nomia melanderi nest near alfalfa ( Medicago sativa (Linnaeus)) (Cane, 1997, 2008; Vinchesi et al ., 2013); and Dieunomia triangulifera nest near sunflowers ( Helianthus annuus (Linnaeus)) (Minckley et al ., 1994). Oddly, however, it is not known whether bees actually use the presence or abundance of host‐plant flowers or foliage when choosing where to nest: they may simply be found alongside their host‐plants because of philopatry, or because they share substrate preferences with their host‐plants.…”
Section: Nest‐site Selection: Which Characteristics Matter?mentioning
confidence: 99%
“…Such research would be especially valuable in agricultural systems, where farming practices can involve mixing the soil to a depth of up to 40 cm during tillage, and the use of agrochemicals to combat insect pests. A few papers have investigated the effect of tillage (Ullmann et al ., 2016; Skidmore et al ., 2019), irrigation (Julier & Roulston, 2009) and pesticides (Willis Chan et al ., 2019) on ground‐nesting bees, but more research is needed on different species of ground‐nesters, other than squash bees, and their reproductive output. We still know little about the effects of agrochemicals on survival of ground‐nesting bees, whether at the underground larval stages or as adults, but recent studies have begun to show impacts of pesticides on bees through exposure to contaminated soil (Anderson & Harmon‐Threatt, 2019; Willis Chan et al ., 2019).…”
Section: Future Directionsmentioning
confidence: 99%
“…The decline in numbers of squash bees is alarming because in 2014 and 2015 we began the hourly bee counts two hours earlier in order to better capture squash bee activity, based on reports in the literature that squash bees started visiting flowers at dawn [12,21], but the numbers of squash bees observed continued to decline. Chan et al [24] found that levels of neonicotinoids found in field soil from seed treatments and soil applications posed a significant hazard through soil contact to squash bees, which nest in the ground, preferring to nest in disturbed soil in cultivated fields [25].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, another study observed similar adult squash bee abundance in tilled and untilled pumpkin fields, and squash bees preferred to nest in irrigated soil near host plants regardless of whether or not the soil was tilled [33]. However, more recent findings suggest that squash bees prefer to nest in tilled soil [34]. Mulching is another ground management practice commonly used in Cucurbita production that may deter or inhibit squash bee nesting.…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple studies have examined the impacts of farm management on squash bees, the scope of investigation has often been limited to one management practice at a time, sample sizes have been relatively low, and results have often been mixed [31][32][33][34]. Here, we used a citizen science survey to determine how squash bee abundance varies according to multiple farm management practices including tillage type, depth, and mulch, and ascertain the distribution of squash bees in Michigan.…”
Section: Introductionmentioning
confidence: 99%